Determinación de la cantidad de residuos sólidos inorgánicos no peligrosos desechados en la carrera de Agrícola de la ESPAM “MFL” - Alcívar Murillo, Marcos Leonardo (2021)
This research was carried out in the Agricultural Engineering career of ESPAM "MFL", site "El Limón", Bolívar canton, Manabí province; Its purpose is to determine the amount of non-hazardous inorganic solid waste generated in said race. For this purpose, three phases were established: Diagnosis of the environmental situation of non-hazardous solid waste of the Agricultural Engineering career, in this case a review of the current regulations was carried out, and then gave way to the application of a interview with the career director and a survey of Agrícola students, ending with the identification of waste generation areas within the career facilities. Characterization of non-hazardous solid waste, for which it began with the location of strategic containers in the different areas of the race, for the subsequent collection and weighing of the waste, data that later made it possible to calculate the per capita production. Design of an Environmental Management Plan for the non-hazardous solid waste of the career, which consists of three programs: Solid Waste Management, Communication and Environmental Training and Follow-up, Control and Monitoring. As results it was obtained that the weekly per capita production is: plastic 0.0404 kg * inhab / day; cardboard 0.0017kg * hab / day; paper 0.0018 kg * inhab / day and glass 0.0023 kg * inhab / day. Concluding that, it is essential to train the student community on the management and final disposal of solid waste, so that it can contribute to the proper management of the same.